Eudiplozoon nipponicum: morphofunctional adaptations of diplozoid monogeneans for confronting their host - Valigurová, Andrea; Vaškovicová, Naděžda; Gelnar, Milan; Kováčiková, Magdaléna; Hodová, Iveta (BMC zoology, 2021)
BACKGROUND: Monogeneans, in general, show a range of unique adaptations to a parasitic lifestyle, making this group enormously diverse. Due to their unique biological properties, diplozoid monogeneans represent an attractive model group for various investigations on diverse biological interactions. However, despite numerous studies, there are still gaps in our knowledge of diplozoid biology and morphofunctional adaptations. RESULTS: In this study, we provide a comprehensive microscopic analysis of systems/structures involved in niche searching, sensing and self-protection against the host environment, and excretory/secretory processes in Eudiplozoon nipponicum. Freeze-etching enabled us to detect syncytium organisational features not visible by TEM alone, such as the presence of a membrane subjacent to the apical plasma membrane (separated by a dense protein layer) and a lack of basal plasma membrane. We located several types of secretory/excretory vesicles and bodies, including those attached to the superficial membranes of the tegument. Giant unicellular glands were seen accumulating predominantly in the apical forebody and hindbody haptor region. Muscle layer organisation differed from that generally described, with the outer circular and inner longitudinal muscles being basket-like interwoven by diagonal muscles with additional perpendicular muscles anchored to the tegument. Abundant muscles within the tegumentary ridges were detected, which presumably assist in fixing the parasite between the gill lamellae. Freeze-etching, alongside transmission electron and confocal microscopy with tubulin labelling, enabled visualisation of the protonephridia and nervous system, including the peripheral network and receptor innervation. Three types of receptor were identified: 1) uniciliated sensory endings with a subtle (or missing) tegumentary rim, 2) obviously raised uniciliated receptors with a prominent tegumentary rim (packed with massive innervation and muscles) and 3) non-ciliated papillae (restricted to the hindbody lateral region). CONCLUSIONS: This study points to specific morphofunctional adaptations that have evolved in diplozoid monogeneans to confront their fish host. We clearly demonstrate that the combination of different microscopic techniques is beneficial and can reveal hidden differences, even in much-studied model organisms such as E. nipponicum.
Keywords: Freeze-etching; Musculature; Ultrastructure; Sensory structures; Immunofluorescence; Tegument; Nervous system; Excretory system; Secretion; Host-parasite interactions